Potential for bowhead whale entanglement in cod and crab pot gear in the Bering Sea. Issue 2 (12th June 2013) - Citta,, John J.; Burns, John J.; Quakenbush, Lori T.; Vanek, Vicki; George, John C.; Small, Robert J.; Heide‐Jørgensen, Mads Peter; Brower, Harry
Abstract Bowhead whales (Balaena mysticetus) of the western Arctic stock winter in ice‐covered continental shelf regions of the Bering Sea, where pot fisheries for crabs (Paralithodes and Chionoecetes spp.) and Pacific cod (Gadus macrocephalus) pose a risk of entanglement. In the winter of 2008–2009 and 2009–2010 the spatial distribution of 21 satellite tagged bowhead whales partially overlapped areas in which pot fisheries for cod and blue king crab (Paralithodes platypus) occurred. However, these fisheries ended before whales entered the fishing areas, thus avoiding temporal overlap. A fishery for snow crab (Chionoecetes opilio) typically runs from January to May and provides the greatest potential for bowhead whales to encounter active pot gear. Tagged whales did not enter the area of the snow crab fishery during this study and generally remained in areas with >90% sea ice concentration, which is too concentrated for crab boats to penetrate. Pack ice sometimes overruns active fishing areas, resulting in lost gear, which is the most likely source of entanglement. The western Arctic stock of bowhead whales was increasing as of 2004; as such, incidental mortality from commercial pot fisheries is probably negligible at this time. Regardless, entanglement may increase over time and should be monitored.